The Concept Of Human Resource Management In The Life Of Business Organizations In The Digital Era - Wa Ode Musmiarny Nilammadi; Othy Happy Dharmaning Savitry; Eni Wuryani (Economic and Bussiness Faculty, Dr Soetomo University, 2024)
The development of digital technology has brought new challenges in managing human resources in the modern era. The concept of HR management has become the main focus of organizations in facing change. The aim of the research is to analyze the concept of HR management in organizational life in the digital era. This research uses descriptive analysis methods to study related literature and explore an in-depth understanding of HR management concepts. The main findings of this research show that human resources have a significant influence on the lifecycle of business organizations in the digital age. In the digital era, the role of human resources is becoming increasingly important because of digital transformation which influences the way work and interactions within organizations. To build a great business organization in the digital era, companies need to take strategic steps that can optimize human resource potential and respond to rapid changes in the business environment. However, in optimizing the potential of human resources there are challenges that need to be faced. To overcome this, a sustainable approach to human resources (Sustainable HRM) emerged.